Research progress on the application of antiplatelet drugs in arteriovenous fistula for hemodialysis - Ma Shi-jie; Deng Fei (Linchuang shenzangbing zazhi)
The number of patients with chronic kidney disease is increasing globally. For patients with end-stage kidney disease， hemodialysis （HD） is the most common kidney replacement therapy. Among the currently common types of clinical vascular access， arteriovenous fistula （AVF） is the most widely used dialysis vascular access worldwide. However， arteriovenous fistula often leads to access dysfunction due to thrombosis. Antiplatelet drugs， due to their positive effect on inhibiting thrombosis， are considered as potential therapeutics to prevent arteriovenous fistula thrombosis. This article reviewed the application of antiplatelet drugs in the treatment of arteriovenous fistula in HD patients.